Personalized medicine in nonalcoholic fatty liver disease - Pirola, Carlos Jose (2022)
The keystone of precision medicine in complex traits is to predict the onset and progression of the disease. While there are different paths toward precision medicine,1 genetic assessment may be among the top strategies. The current knowledge of the complete human genome sequence and the availability of next-generation sequencing technologies2 to decipher individual patients’ genetic make-up also invite fully integrated genomic medicine. Therefore, patients may be classified into high or low risk for disease onset or severity, and therapeutic interventions can be personalized. Most importantly, precision medicine must ensure health benefits across geography, ethnicity, age, and gender...